2001
DOI: 10.1002/mrd.1062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cell cycle dependent kinases inhibitor on nuclear and cytoplasmic maturation of porcine oocytes

Abstract: The aims of this study were to assess the effectiveness of roscovitine, a potent inhibitor of cell cyclin kinases, to prevent meiotic resumption in porcine oocytes, and to test the subsequent fertilisability and developmental competence of these oocytes. Roscovitine blocked porcine oocytes at the GV stage during 22-44 hr of culture. This effect was dose-dependent, and a concentration of 25 microM was sufficient to prevent meiotic resumption in 92+/-5% of the oocytes after 22 hr in the presence of EGF and FSH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 45 publications
5
55
0
1
Order By: Relevance
“…In fact, GV oocytes treated transiently with roscovitin, an inhibitor of MPF, display a delay in GVBD and cytoskeletal characteristics more similar to in vivo matured oocytes (Sanfins et al, 2004). Consistently, it has been described in the pig (Marchal et al, 2001), cow (Ponderato et al, 2001) and horse (Franz et al, 2003) that temporary arrest at the GV stage with roscovitin at the beginning of the maturation period increases the developmental potential of IVM oocytes. The implications of these findings are least two-fold.…”
Section: Meiotic Arrest and Progressionsupporting
confidence: 64%
“…In fact, GV oocytes treated transiently with roscovitin, an inhibitor of MPF, display a delay in GVBD and cytoskeletal characteristics more similar to in vivo matured oocytes (Sanfins et al, 2004). Consistently, it has been described in the pig (Marchal et al, 2001), cow (Ponderato et al, 2001) and horse (Franz et al, 2003) that temporary arrest at the GV stage with roscovitin at the beginning of the maturation period increases the developmental potential of IVM oocytes. The implications of these findings are least two-fold.…”
Section: Meiotic Arrest and Progressionsupporting
confidence: 64%
“…MPF is required for oocyte GVBD. The effect of roscovitine on the maintenance of oocyte meiotic arrest and oocyte developmental competence has been previously assessed in pigs using different concentrations, inhibitory periods and sources of oocytes [8][9][10][11][12][13]20]. However, the molecular basis of MPF action is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, the data for the interplay of these two kinases in oocytes are still controversial. Previous studies using pig oocytes have focused primarily on the dynamic changes in MAPK and MPF activities and on the effects of inactivation of these two kinases on porcine oocyte maturation in terms of nuclear maturation, microtubule organization and oocyte developmental competence [5][6][7][8][9][10][11][12][13]. The underlying molecular mechanisms, such as the cytoplasmic maturation and regulation of maternal gene expression, remain to be reported.…”
mentioning
confidence: 99%
“…In fact, we observed different expression patterns of mRNA between meiotic arrested oocytes and non-treated oocytes (unpublished data). In addition, Marchal et al [88] have also shown that immature porcine oocytes synthesize some proteins during meiotic arrest by roscovitine, a potent inhibitor of cyclindependent kinase.…”
Section: Meiotic Arrestmentioning
confidence: 99%